Respuesta :
Answer: z = -5/-3
Step-by-step explanation:
(3z−11)+(6−6z)
3z - 11 + 6 - 6z
- 6z + 3z - 11 + 6
- 3z - 5
z = -5/-3
The expression which represents the sum (3z−11)+(6−6z) is; -3z -5
According to the question;
- We are required to determine the sum of the expression (3z−11)+(6−6z).
Evidently, the expression above is a one-variable expresssion.
As such, the sum can be evaluated by outright addition of like terms as follows;
(3z−11)+(6−6z).
= 3z + (-6z) -11 + 6.
= -3z - 5.
Read more:
https://brainly.com/question/17678458